3 + 5= 5+3

2 + (-2)=0

6 -3+3-6

5 +0=0

2+(4+5)=(2 + 4 )+5

3 x 5 = 5 x 3

10 / 2 =2 /10

2(5 X 3) = (2 x 5)(3)

2(1/2)=0

1 X 3 = 3

3 + 5= 5+3

2 + (-2)=0

6 -3+3-6

5 +0=0

2+(4+5)=(2 + 4 )+5

3 x 5 = 5 x 3

10 / 2 =2 /10

2(5 X 3) = (2 x 5)(3)

2(1/2)=0

1 X 3 = 3

Tutors, please sign in to answer this question.

Middletown, CT

Hi Travina;

2-2=0

6-6=-3+3, 0=0

5(0)=0, 0=0

2+(9)=(6)+5

11=11

15=15

10/2=10/2

2(15)=(10)(3)

30=30

2(1/2)=1

- Math Help 5461
- Math 9892
- Math Word Problem 4511
- Math Problem 1021
- Math Question 799
- Math Help For College 1400
- Mathematics 580
- Math Answers 417
- Maths 692
- Precalculus 1595